The Dance with Community The Contemporary Debate in American Political Thought - Fowler, Robert Booth (University Press of Kansas, 1991)
Contemporary intellectuals have rushed to embrace the concept of *#8220;community." What does this tell us about American political thought? Why are intellectuals uneasy with modern liberal individualism and its institutional policy results? Why is political intellectual discourse dominated today by complaint?In The Dance with Community Robert Booth Fowler reflects upon these and related questions. "My goal," he writes, "is to present contemporary political thought about community for what it is-a conversation interactive, spirited, and sometimes tough."There have been many interpretations of the muchdiscussed decline in community spirit. Rather than offer another, Fowler steps back to look at the debate itself. He examines from the perspective of an intellectual historian the attention to community in current American political thought and explores the setting of that attention.He also identifies five alternative models of community integral to the current debates and sketches a clear image of each-its relationship to others, the logic of its appeal, and its emphases and problems. In each instance he places the model into the larger conversation over alternative communities and the value of community itself.